Troubling the family : the promise of personhood and the rise of multiracialism - Ibrahim, Habiba (Difference incorporated., 2012)
Troubling the Family argues that the emergence of multiracialism during the 1990s was determined by underlying and unacknowledged gender norms. Opening with a germinal moment for multiracialism -- the seemingly instantaneous popular appearance of Tiger Woods -- Habiba Ibrahim examines how the shifting status of racial hero for black and multiracial communities makes sense only by means of an account of masculinity.